Personal and social development in physical education and sports : a review study - Chapelle, Laurent (2020)
This review provides an overview of the existing literature on school-aged children's and youth's (i.e. 6- to 18-year-olds) personal and social development within the context of physical education and sports. A total of 4359 non-duplicate articles were retrieved from six databases. After the title, abstract and full text screening, 88 articles met the inclusion criteria and were included for further analysis. Articles had to be published in a peer-reviewed journal between 1 January 2008 and 6 December 2017. The 88 studies used several study designs, methods and instruments to investigate a variety of concepts related to personal and social development. Concepts were grouped into the following 11 themes: work ethic; control and management; goal-setting; decision-making; problem-solving; responsibility; leadership; cooperation; meeting people and making friends; communication; and prosocial behaviour. The main findings for each of the 11 themes are reported, and limitations and implications are provided to guide researchers and practitioners in their future work